Association between Lipid Profiles and Serum Urate: A Cross-Sectional Study in Southwestern China - Jiying Qi; Xiaojuan Dai; Binbin Zhou; Yang Su; Zhen Xie; Dongmei Liu (International Journal of Endocrinology)
Objective. The relationship between lipid profiles and serum urate has not been fully investigated. This study aims to investigate the sex- and age-specific association between lipid profiles and serum urate. Methods. This was a cross-sectional study involving 122,351 participants aged 18–99 years from a check-up centre in Southwestern China. Generalized additive models and smooth curve fitting were conducted to explore the association between components of lipid profiles and serum urate. Furthermore, multivariate linear and logistic regression models were also performed. Results. In generalized additive models, the fitted smoothing curves showed that serum urate fluctuated in a small range with total cholesterol, LDL-C, or HDL-C raising. After adjusting for confounders, the differences in serum urate progressively increased with raising serum triglycerides quartiles. The likelihood (odds ratio, OR) for developing serum urate > 420 μmol/L significantly increased in the highest quartile of triglycerides than in the lowest quartile, in hypertriglyceridemia than in normal triglycerides, and with 1 mmol/L increment in triglycerides in all sex- and age-specific groups. Furthermore, the increased OR (95% confidence interval) was higher in females than in males compared with their respective controls. Conclusions. Serum urate and the likelihood for developing serum urate >420 μmol/L increased with triglycerides raising. Females were in a higher likelihood for developing serum urate >420 μmol/L than males with raising triglycerides. With changes in total cholesterol, LDL-C, or HDL-C, serum urate fluctuated in a small range.